Determination of Financial Stability Index Between Southeast Asian Countries (ASEAN 6) and Its Intracorrelation - Suhartoko, Y.B.; Pratikto, Adji; Selvi Susanti Wira, Luciana (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2022)
The Economic crisis has impacted the disruption of the stability of a country's financial system, including ASEAN countries. In Indonesia, there is a Financial System Stability Committee (KSSK) whose duties are to coordinate monitoring and maintaining financial system stability. KSSK has the authority to set the criteria and indicators for assessing financial system stability conditions concerning the financial system's stability. The second authority is to evaluate the condition of financial system stability based on input from each member of the Financial System Stability Committee, along with supporting data and information. As an economic area with history, ASEAN countries certainly have a relationship, either strong or weak. This study conducted calculations of the financial stability index (Aggregate Financial Stability Index) built from the Morris framework (2010) consisting of sub-index Financial Development Index, Financial Vulnerability Index, Financial Soundness Index, World Economic Climate Index. The calculation results showed that in ASEAN 6, there were fluctuations in financial stability, and there were variations in the correlation of financial stability. Therefore, improving the financial stability in Indonesia needs to consider the existence of financial stability in other countries.